2014
DOI: 10.1371/journal.pntd.0003230
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Neutralizing Antibody Levels Associated with Protection from Infection in Thai Cluster Studies

Abstract: BackgroundLong-term homologous and temporary heterologous protection from dengue virus (DENV) infection may be mediated by neutralizing antibodies. However, neutralizing antibody titers (NTs) have not been clearly associated with protection from infection.Methodology/Principal FindingsData from two geographic cluster studies conducted in Kamphaeng Phet, Thailand were used for this analysis. In the first study (2004–2007), cluster investigations of 100-meter radius were triggered by DENV-infected index cases fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 38 publications
3
64
0
Order By: Relevance
“…A recent index-cluster study in Thailand found that individuals with symptomatic infections had lower preinfection NAb titers than a comparable group of individuals likely, but not definitely, exposed to DENV but who did not become ill (18). However, because of study limitations, these findings collectively do not provide definitive proof of the relationship between NAb titers and protection: The protective effect was not consistently observed against all DENV serotypes (17); the DENV-negative individuals may not have been exposed to DENV (18); and the magnitude of NAb titers was not directly analyzed (12,19). Beyond dengue cohort studies, there remains concern that NAb titers measured with nonhuman cell substrates are not as biologically relevant (13).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A recent index-cluster study in Thailand found that individuals with symptomatic infections had lower preinfection NAb titers than a comparable group of individuals likely, but not definitely, exposed to DENV but who did not become ill (18). However, because of study limitations, these findings collectively do not provide definitive proof of the relationship between NAb titers and protection: The protective effect was not consistently observed against all DENV serotypes (17); the DENV-negative individuals may not have been exposed to DENV (18); and the magnitude of NAb titers was not directly analyzed (12,19). Beyond dengue cohort studies, there remains concern that NAb titers measured with nonhuman cell substrates are not as biologically relevant (13).…”
Section: Discussionmentioning
confidence: 95%
“…Previous longitudinal cohort studies in Thailand found that preinfection NAb titers reduce the risk of severe disease (17), whereas studies in Sri Lanka and Peru found that the number of DENV serotypes that were detectably neutralized reduced the risk of symptomatic compared with inapparent 2°DENV infection (12,19). A recent index-cluster study in Thailand found that individuals with symptomatic infections had lower preinfection NAb titers than a comparable group of individuals likely, but not definitely, exposed to DENV but who did not become ill (18). However, because of study limitations, these findings collectively do not provide definitive proof of the relationship between NAb titers and protection: The protective effect was not consistently observed against all DENV serotypes (17); the DENV-negative individuals may not have been exposed to DENV (18); and the magnitude of NAb titers was not directly analyzed (12,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong evidence supports a role for neutralizing antibodies and the 50% neutralizing (PRNT 50 ) titer is widely adopted as a surrogate marker for vaccine efficacy (11)(12)(13). Although the presence of neutralizing antibodies may be associated with a lower risk of disease, a clear correlation between a defined level of neutralization and protection from any serotype remains to be established (14,15). In particular, CYD-TDV (Dengvaxia), the first human-approved DENV vaccine, elicited generally high neutralizing titers in vaccinees but the overall protective efficacy across all 4 DENV serotypes was only 60.3% (16).…”
Section: Introductionmentioning
confidence: 99%
“…It continues to be widely used in clinical, epidemiological and entomological studies [6][7][8][24][25][26][27][28][29]. Nonetheless, due to the accumulated spatiotemporally-dependent changes in the virus genome, continuous monitoring of assay sensitivity is required to ensure the validity and accuracy of the assay.…”
Section: Discussionmentioning
confidence: 99%